Pengaruh Influencer Keuangan dan Pengetahuan Keuangan terhadap Perilaku Investasi (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis di Universitas Trunojoyo Madura) - Ramadhita, Anditsani Firmansyah Sam; Nugroho, Prasetyo (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
This study aims to analyze the influence of financial Influencers and financial knowledge on the investment behavior of students in the Faculty of Economics and Business at Universitas Trunojoyo Madura during the odd semester of 2024. In the post-COVID-19 digital era, financial information has become increasingly accessible through social media, attracting Millennials and Gen Z to enhance their financial literacy and begin investing. Financial Influencer s play a crucial role in educating the public about the world of investment, while financial knowledge is believed to influence individuals' investment decisions. This research examines the relationship between these two factors and students' investment behavior using quantitative methods with multiple regression analysis. The findings reveal that financial Influencers significantly influence students' investment behavior. Students exposed to financial educational content on social media tend to be more proactive in making investment decisions. Additionally, financial knowledge has also been proven to significantly impact more rational investment behavior aligned with their risk profiles. Overall, both financial Influencer s and financial knowledge collectively influence the investment behavior of students in the Faculty of Economics and Business at Universitas Trunojoyo Madura. These findings indicate that strengthening financial education and content provided by financial Influencers can be key factors in increasing student awareness and participation in investments.